(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
The study investigated the production status, problems and prospects of turkey production in Bangladesh following survey and multistage sampling procedure. Average flock size, weight of a tom and hen were 15.34±2.38, 6.58±0.15 and 2.39±0.06 kg, respectively. Commercial, homemade, and both homemade and commercial feed were used by 21.74, 30.43 and 47.83% farmers, respectively. Both tom and hen attained puberty at 7.22±0.06 months, a hen laid 69.46±0.78 eggs per annum and weight of each egg was 66.13±0.63 g. Fertility and hatchability of eggs were 50±3 and 32±1%, respectively. Male and female ratio maintained 1:4.60±0.17. Main reasons of lower hatchability were low egg fertility, faulty incubation, and both low egg fertility and faulty incubation as per 50.0, 21.7 and 28.3% farmers, respectively. None of the farmers used artificial insemination (AI) except natural breeding. Main advantages of turkey rearing over other poultry species were low disease, high market price, low feeding cost and low mortality according to 41.3, 28.3, 17.4 and 13.1% farmers, respectively. While 36.9% farmers had encountered disease, 80.4% had not used vaccine. An egg, a poult and an adult turkey were sold at BDT 76.2±1.79, 838.5±22.8 and 2587.2±74.8, respectively. In fact, turkey production is still at primitive stage which is characterized by poor housing, feeding, breeding and healthcare practices, so vigorous public extension service, training, research and marketing strategies are immediately needed to improve this sector in Bangladesh. Res. Agric., Livest. Fish.4(2): 77-90, August 2017